2020
DOI: 10.3390/cancers12020314
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Estrogen Receptor Status on Circulatory Immune and Metabolomics Profiles of HER2-Positive Breast Cancer Patients Enrolled for Neoadjuvant Targeted Chemotherapy

Abstract: HER2-positive breast cancer (BC) represents a heterogeneous cancer disease. In an attempt to identify new stratification models useful for prognosis and therapeutic strategy, we investigated the influence of estrogen receptor (ER) status on the host immune and metabolomics profile of HER2-positive BC patients enrolled for neoadjuvant targeted chemotherapy (NATC). The study enrolled 43 HER2-positive BC patients eligible for NATC based on the trastuzumab-paclitaxel combination. Baseline circulatory cytokines and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 62 publications
1
27
0
1
Order By: Relevance
“…The observed citrulline shortage in H-Risk patients may be the result of tumor-patient metabolic interplay. Indeed, in cancer patients, the metabolic reprogramming that sustains cancer cell proliferation, survival and metastasis not only involves cancer cells but also affects the whole host organism [ 24 ]. A tumor is a high energy-demanding tissue that requires, besides glucose, other carbon intermediates, which may result in deficiencies of certain metabolites in the blood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed citrulline shortage in H-Risk patients may be the result of tumor-patient metabolic interplay. Indeed, in cancer patients, the metabolic reprogramming that sustains cancer cell proliferation, survival and metastasis not only involves cancer cells but also affects the whole host organism [ 24 ]. A tumor is a high energy-demanding tissue that requires, besides glucose, other carbon intermediates, which may result in deficiencies of certain metabolites in the blood.…”
Section: Discussionmentioning
confidence: 99%
“…Such a profile describes the biochemical events occurring in an organism and it reflects the complex interactions among age, sex, gene transcription, protein expression, physio-pathological conditions, including gut microbiome activity and environment effects [ 20 , 21 ]. These features make metabolomics an important tool to assess the patients’ phenotypes and it has already been widely used to identify diagnostic cancer signatures and prognostic biomarkers [ 22 , 23 , 24 , 25 ]. However, only a few metabolomics studies have been reported for sarcoma and they mainly regard in vitro investigations [ 26 , 27 ]; those performed in a clinical setting were focused on specific sarcoma subgroups [ 28 , 29 , 30 ] and limited only to gemcitabine treatment [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Study of the metabolomic profile of patients with triple-negative BC has further refined the molecular characterization of this BC subtype that accounts for 10–22% of all diagnosed BC and has the worst survival rate [ 115 ]. A recent study on plasma unravels how ER status impacts on the metabolomic profiles of patients with HER2-positive BC, with metabolomic data also studied in association with levels of circulatory cytokines [ 99 ]. Blood metabolomics has also shown how high expression of the receptor for the inositol 1, 4, 5 Trisphosphate, of which deregulation promotes tumor growth and aggressiveness, influences the host system metabolome by increasing lipoprotein content and the levels of lactate, lysine, and alanine and by decreasing the levels of pyruvate and glucose [ 111 ].…”
Section: Nmr Metabolomics Of Blood Plasma/serummentioning
confidence: 99%
“…Briefly, after thawing, 10 µL of serum was transferred into a filter on the upper well of a 96-well sandwich plate. A mixture of internal standards labelled isotopically with deuterium, 13 C or 15 N was already present in each well. Nitrogen steam drying of filters was followed by derivatization of amino acids with 5% phenyl isothiocyanate (PTC) and a second drying step.…”
Section: Targeted Serum Metabolomics Profile Analysismentioning
confidence: 99%
“…Hence, the blood metabolites composition represents a hypothetical source of biomarkers and the understanding of how metabolites and their concentrations change under RT interventions may allow the discovery of potential biomarkers for RT efficacy and toxicity. The effect of anticancer drug treatments on local and systemic metabolism have been widely investigated in different cancer types by the metabolomics tool [ 13 , 14 , 15 , 16 ]. Nevertheless, only a few broad-based metabolomics studies have been so far reported about the effects of RT on the host system [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ] and none in the specific MPM field.…”
Section: Introductionmentioning
confidence: 99%